Daddy's home 2 [videorecording (DVD)] - Anders, Sean, 1969-; Anders, Sean, 1969-; Wahlberg, Mark, 1971-; Ferrell, Will, 1967-; Ferrell, Will, 1967-; Cardellini, Linda, 1975-; Lithgow, John, 1945-; Gibson, Mel (Paramount, 2018)
Dusty and Brad agree to have Christmas in one house so their kids do not have to travel, but their plans are thrown into chaos when Dusty's macho dad and Brad's ultra-affectionate dad arrive.